Social benefits of living in the metaverse: The relationships among social presence, supportive interaction, social self-efficacy, and feelings of loneliness - Oh, Hyun Jung; Kim, Junghwan; Chang, Jeongheon J.C.; Park, Nohil; Lee, Sangrock (Computers in human behavior, 2023)
In the context of South Korea, the present study investigated the social benefits of utilizing the two popular metaverse platforms, Roblox and Zepeto. Focusing on young generations, millennials and Generation Z, it examined if enhanced social presence in the metaverse facilitates supportive interactions among young users, and if their active engagement in supportive interactions in the metaverse reduces their feelings of loneliness through enhanced social self-efficacy. A structural equation modeling with 300 cases of young Koreans yielded the following results. First, the social presence young users experienced in the metaverse platform significantly predicted the amount of supportive interactions they engaged in the metaverse. Second, the amount of supportive interactions in the metaverse positively predicted users' perception of social self-efficacy. Finally, social self-efficacy mediated the relationship between the amount of supportive interactions in the metaverse and young people's feelings of loneliness. The findings of this study provide implications on how to design features and services in the metaverse to maximize its social benefits to young users. •The metaverse benefits young generations by enhancing their sense of social presence within the virtual environment.•The sense of social presence in the metaverse facilitated supportive interactions among young users.•The amount of supportive interactions in which users engaged in the metaverse enhanced users' social self-efficacy.•Social self-efficacy mediated the effect of supportive interactions in the metaverse on users' feelings of loneliness.